2016
DOI: 10.4103/0970-2113.192878
|View full text |Cite
|
Sign up to set email alerts
|

The burden of segregated respiratory diseases in India and the quality of care in these patients: Results from the Asia-Pacific Burden of Respiratory Diseases study

Abstract: Background:Chronic respiratory diseases such as asthma, allergic rhinitis (AR), chronic obstructive pulmonary disease (COPD), and rhinosinusitis are becoming increasingly prevalent in the Asia-Pacific region. The Asia-Pacific Burden of Respiratory Diseases study examined the disease and economic burden of AR, asthma, COPD, and rhinosinusitis across the Asia-Pacific and more specifically India.Objectives:To estimate the proportion of adults receiving care for asthma, AR, COPD, and rhinosinusitis and assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Some of the country-specific findings have been reported for India, Korea, Taiwan, and Thailand [13-16]. Here we report additional country-specific findings as well as the results differentiated between general practitioners (GP) and specialists regarding country-specific practice patterns, patient characteristics, HCRU, and health-related QoL for patients with a primary diagnosis of AR, asthma, COPD, or rhinosinusitis.…”
Section: Introductionmentioning
confidence: 52%
“…Some of the country-specific findings have been reported for India, Korea, Taiwan, and Thailand [13-16]. Here we report additional country-specific findings as well as the results differentiated between general practitioners (GP) and specialists regarding country-specific practice patterns, patient characteristics, HCRU, and health-related QoL for patients with a primary diagnosis of AR, asthma, COPD, or rhinosinusitis.…”
Section: Introductionmentioning
confidence: 52%
“…8,12 Present study revealed that chronic cough and phlegm was significantly higher among current and ex-smokers compared to non-smokers. 4,8,9,11,13,14 Cigarette smoke contains thousands of chemical components, which can irritate and activate macrophages and cells that make up the lining of the airways (epithelial cells). This causes the cells to release multiple types of cytokines, which are small signaling proteins that cause the airway lining to thicken and airways to become inflamed.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the socioeconomic burden on healthcare resources arising from these respiratory diseases is essential to identify effective interventions, plan priorities, and strategically allocate funds and resources to reduce the burden of these respiratory diseases in India. While several studies have addressed prevalence, diagnosis, and treatment of the above respiratory diseases in India, no studies to date have explored the burden of care in adults who present to healthcare professionals (HCP) using one standard protocol 5 . Respiratory diseases constitute a major cause of morbidity and mortality worldwide, the top five respiratory diseases accounting for 17.4% of all deaths and 13.3% of all disability-adjusted life years in the year 2000 6 .…”
Section: Introductionmentioning
confidence: 99%